Participatory Community-Based Tourism Development in Bang Len Community, Bang Len Subdistrict, Bang Yai District, Nonthaburi Province - Jullasikkee, Manachanok; Nutchanart, Apinya; Charkhamrun, Supannikar (Rajapark Journal, 2025)
This research aimed to 1) study the community context of Bang Len, Bang Len Subdistrict, Bang Yai District, Nonthaburi Province; 2) analyze the community-based tourism (CBT) potential of Bang Len; 3) develop tourism routes and activities through community-based participatory approaches in Bang Len; and 4) evaluate tourist satisfaction with those routes and activities. The study employed a mixed-methods approach. The purposively selected sample consisted of 37 participants, including community leaders, entrepreneurs, relevant agencies, and tourists. Data were collected through semi-structured interviews, participant observation, focus group discussions, and tourist surveys. Qualitative data were analyzed through content analysis and SWOT analysis, while quantitative data were analyzed using descriptive statistics - percentage, mean, and standard deviation. The findings revealed that 1) Bang Len was a long-established riverside community along Khlong Om Non, characterized by traditional agricultural lifestyles and a strong emphasis on preserving local culture. 2) The community’s CBT potential lay in its unique natural and cultural resources, strong local cohesion, and internal management, along with external support from relevant agencies. 3) Based on the findings, a one-day tourism route titled “Suan Kaew, Suan Bua: Riverside Life of Khlong Om Non” was developed, featuring interconnected attractions and experiential learning activities rooted in local wisdom. 4) The overall tourist satisfaction toward the route and activities was high, with tourism activities receiving the highest level of satisfaction.